Can PTSD be prevented? A novel approach to increasing physiological resilience: a pilot study - Dust, Mark (Frontiers in Psychology, 2023)
Much of the U.S. adult population will experience a traumatic event at some point in their lives, resulting in about 20 million people developing posttraumatic stress disorder (PTSD) and costing over $143 billion for healthcare. The Community Resilience Model (CRM) and Mental and Emotional Self-Management (MESM) are potential novel solutions for stemming the tide of PTSD diagnoses resulting from a traumatic event. This pilot study was conducted to examine the phasic and tonic changes in cardiac vagal tone in a non-traumatized sample population (N = 83) after a one-week intervention. Group comparisons were conducted between the CRM (n = 26), MESM (n = 34), and Control (n = 23) conditions. Participants ranged in age from 18 to 30. A phasic effect on cardiac vagal tone was found for the MESM condition within subjects, but not for the CRM or control conditions. A tonic effect on cardiac vagal tone was not found within subjects amongst the three conditions. The phasic effect in the MESM condition was significantly different between itself and the CRM and control groups as well. No tonic effects on cardiac vagal tone were found between conditions either. These results suggest cardiac vagal tone responds to focused breathing in the moment only, but more research with larger sample sizes, longer intervention duration, and better methods to track home practice compliance are needed before one accepts the insignificant results as valid. This pilot study can serve as an introduction to the study of physiological processes that might be trainable to increase resilience in non-traumatized population and serve as a springboard for future studies of physiological resilience to traumatic stress.